1998
DOI: 10.1093/emboj/17.9.2504
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli SRP and SecB targeting pathways converge at the translocon

Abstract: Two distinct protein targeting pathways can direct proteins to the Escherichia coli inner membrane. The Sec pathway involves the cytosolic chaperone SecB that binds to the mature region of pre-proteins. SecB targets the pre-protein to SecA that mediates preprotein translocation through the SecYEG translocon. The SRP pathway is probably used primarily for the targeting and assembly of inner membrane proteins. It involves the signal recognition particle (SRP) that interacts with the hydrophobic targeting signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
255
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(273 citation statements)
references
References 63 publications
16
255
1
1
Order By: Relevance
“…The substrate speci¢city of SRP for membrane proteins may re£ect the higher a¤nity of SRP for relatively hydrophobic signal sequences. Consistent with this idea, in vitro crosslinking studies have shown that more hydrophobic signal sequences are better crosslinked to Ffh [9,10]. Furthermore, crosslinking to trigger factor was unaffected by hydrophobicity [9].…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…The substrate speci¢city of SRP for membrane proteins may re£ect the higher a¤nity of SRP for relatively hydrophobic signal sequences. Consistent with this idea, in vitro crosslinking studies have shown that more hydrophobic signal sequences are better crosslinked to Ffh [9,10]. Furthermore, crosslinking to trigger factor was unaffected by hydrophobicity [9].…”
Section: Introductionmentioning
confidence: 67%
“…The 9L1A signal sequence has been known to crosslink well to Ffh [10], suggesting that it may follow a SRP-dependent pathway. However, under the conditions used here, transport of PhoA with the 9L1A signal sequence did not appear sensitive to limiting amounts of Ffh.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a functional test of the interaction of SRP with ribosome nascent-chain complexes (RNCs) and with FtsY, we have used the protein targeting assay (Valent et al+, 1998)+ RNCs were prepared in E. coli extracts by translating truncated mRNA coding for FtsQ, an integral inner membrane protein+ SRP binding to RNCs is indicated by DSS crosslinking of the radioactively labeled nascent signal sequence to Ffh in SRP, and the productive interaction of the RNC-SRP complex with FtsY is indicated by the disappearance of the crosslink in the presence of both FtsY and inverted vesicles of the E. coli plasma membrane containing the translocon (Valent et al+, 1998)+ In the control experiment with wild-type SRP, the nascent signal peptide was efficiently crosslinked to Ffh, as shown by the presence of the 62-kDa Ffh-NC crosslinked product, and the crosslinked product disappeared completely upon addition of FtsY, indicating successful targeting of RNCs to the translocon (Fig+ 4); the results are summarized in Table 1+ With SRP containing mutant 4+5S RNA(UUCG), as with the other mutants, crosslinking was quite efficient, indicating that binding of SRP to RNCs was undisturbed, but no release of nascent chain from SRP was observed upon addition of 1 mM FtsY (threefold excess over SRP)+ Also, in the case of the UUUU mutant, there was no efficient release of the nascent chain, and partial release was observed for the CUUC mutant+ Single or double base substitutions at any position of the tetraloop sequence had no effect on the release of the nascent chain from SRP except for the GAAU mutant, where the release was somewhat less efficient+ Targeting assays were also performed at ten times higher concentration of FtsY (10 mM; 30-fold excess over SRP)+ Under these conditions, the extent of targeting was increased to full activity for 4+5S RNA with the CUUC and GAAU substitutions, and to partial activity with UUUU, whereas with UUCG, again no targeting was observed (Fig+ 4; Table 1)+ The crosslinking data show that none of the tetraloop mutations studied affected the binding of SRP to the nascent chain on the ribosome+ The results of the targeting assays in the presence of FtsY, therefore, suggest that the exchange of the wild-type GGAA sequence of 4+5S RNA for UUCG decreases the affinity of SRP for FtsY to an undetectable level, and the exchange for CUUC, GAAU, and UUUU leads to intermediate affinities+…”
Section: Srp Interaction With Ribosome Nascent-chain Complexes and Mementioning
confidence: 99%
“…The signal recognition particle (SRP) functions in cotranslational targeting of ribosomes synthesizing proteins with an N-terminal targeting signal to the membrane of the endoplasmic reticulum (ER) in eukaryotes and to the plasma membrane in prokaryotes (Walter & Johnson, 1994;Rapoport et al+, 1996;de Gier et al+, 1997)+ SRP recognizes an N-terminal targeting peptide emerging from the translating ribosomes, and, subsequently, the ribosome-SRP complex binds to the SRP receptor at the membrane+ Compared to mammalian SRP (Walter & Blobel, 1983), bacterial SRP is of simpler composition and consists of one RNA (4+5S RNA) and one protein (Ffh), which share homologies with their respective eukaryotic functional counterparts, 7S RNA (Poritz et al+, 1988) and SRP54 protein (Bernstein et al+, 1989;Römisch et al+, 1989)+ The majority of proteins secreted from bacteria appears to be exported posttranslationally by the SecB pathway, and the SRP pathway may be used for a few proteins only+ However, the SRP pathway in Escherichia coli is essential for membrane insertion of several inner membrane proteins (Ulbrandt et al+, 1997;Beck et al+, 2000), and the SRP and SecB pathways use the same translocon for protein translocation (de Gier et al+, 1998;Valent et al+, 1998)+ Ffh and the bacterial SRP receptor, FtsY, belong to the group of SRP-related GTPases+ Their G domains contain an insertion, I box, in the effector loop, and an N-terminal four-helix N domain that is closely packed against the G domain (Freymann et al+, 1997;Montoya et al+, 1997)+ The M domain of Ffh contains the binding sites for the signal sequence and the SRP RNA (Keenan et al+, 1998)+ The structure of the M domain of human SRP54 is similar (Clemons et al+, 1999)+ SRP and FtsY were reported to moderately stimulate each other's GTPase activity (Powers & Walter, 1995), and a conformational change in the I box region of FtsY upon binding to SRP was demonstrated by fluorescence measurements (Jagath et al+, 2000)+ Eukaryotic SRP RNA (7S RNA) can be divided into four structural domains (I-IV) (Poritz et al+, 1988) or eight helices (Larsen & Zwieb, 1991), of which the most conserved domain IV (or helix 8) is present in all SRP RNAs, including 4+5S RNA from E. coli. The structure of an RNA fragment comprising domain IV of E. coli 4+5S RNA has been determined by NMR (Schmitz et al+, 1999a(Schmitz et al+, , 1999b)+ Genetic and bioch...…”
Section: Introductionmentioning
confidence: 99%